MENINGKATKAN HASIL BELAJAR PKN MELALUI MODEL PEMBELAJARAN ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION DI KELAS VII2 SMPN 1 GUNUNG TULEH - Rohana Rohana; Muhammad Arif (STKIP Pesisir Selatan, 2018)
This research begins with the problem of low PKN learning outcomes in Class VII2 SMPN 1 Gunung Tuleh. This study aims to determine the results of student learning through learning model Active Learning Type Role Reversal Question. This research includes classroom action research. This study was conducted in two cycles. Each cycle consists of two meetings, each of which includes planning, action, observation, and reflection. Data collection techniques with observation, documentation, and tests. Data analysis conducted in this research is reduction, data presentation and conclusion. The results of research on that improvement of learning outcomes can be seen from the average value of student evaluation results that have increased in each cycle. Student learning result through learning model of Active Learning Role Type Reversal Question at pre cycle stage of 30,77% (67,77) in cycle I with complete learn student that is 53,85% (72,81) and at cycle II mastery learn student ie 92.31% (82.50). Thus, the Active Learning Model Role Reversal Question model can make students feel easier to understand the material presented by the teacher. The results of this study indicate that the use of Active Learning Model Role Reversal Question type with reword action can improve learning outcomes in class VII2 SMPN 1 Gunung Tuleh